An Evaluation of Remotely Sensed and In Situ Data Sufficiency for SGMA‐Scale Groundwater Studies in the Central Valley, California. (7th January 2021) - Kim, Kyra H.; Liu, Zhen; Rodell, Matthew; Beaudoing, Hiroko; Massoud, Elias; Kitchens, James; Dudek, Marissa; Saylor, Patrick; Corcoran, Forrest; Reager, John T.
Abstract: California's Central Valley aquifer is a critical freshwater resource for the state, providing drinking water to 6.5 million residents and irrigation water for more than half of the nation's produce. Increasing demands have led to a steady decline of aquifer water levels, leading to irreversible compaction and land subsidence. The Sustainable Groundwater Management Act of California (SGMA), instituted in 2014, requires high‐priority regions to establish sustainability plans by 2020–2022 that mitigate groundwater depletion and land subsidence. Many regions within the Central Valley lack groundwater monitoring wells or continuous well data, rendering in situ monitoring challenging. When combined with other data, National Aeronautics and Space Administration's Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On missions provide valuable information about groundwater storage changes at a subbasin scale. Interferometric Synthetic Aperture Radar measurements can map land subsidence, and Global Positioning System can be used to estimate crustal uplift. Yet, all of these measurements have differences in resolution, coverage, discretization, and record length. Here we assess the various datasets that are potentially useful for Central Valley subbasin groundwater monitoring and provide an analysis of gaps and other issues in regard to their suitability for SGMA‐related analysis. Finally, we offer the next steps and recommendations on data treatment and integration. Abstract : Research Impact Statement : Use of NASA datasets detailing groundwater depletion and land subsidence allows policy makers to readily assess subbasin scale details on water resources management when in situ data are lacking.